Pulsed laser deposition of epitaxial Cr2AlC MAX phase thin films on MgO(111) and Al2O3(0001). Issue 8 (3rd August 2021) - Stevens, Marc; Pazniak, Hanna; Jemiola, Alexander; Felek, Merve; Farle, Michael; Wiedwald, Ulf
Abstract : Epitaxial Cr2 AlC MAX phase thin films were grown on MgO(111) and Al2 O3 (0001) by pulsed laser deposition (PLD) at 600°C. X-ray diffraction and morphology studies of Cr2 AlC thin films on MgO (111) reveal phase purity, columnar growth, the epitaxial relation Cr2 AlC(0001) || MgO(111) and Cr2 AlC [11-20] || MgO[10-1] and similar growth behaviour on Al2 O3 (0001). Resistivity measurements show semiconductor-like behaviour for 10 and 20 nm thick films, and metallic-like behaviour for thicker films, suggesting a percolation thickness slightly above 20 nm. Our results demonstrate the potential of PLD as a novel method for the growth of epitaxial MAX phase thin films. GRAPHICAL ABSTRACT: IMPACT STATEMENT: Pulsed Laser Deposition is applied to grow phase pure and epitaxial Cr2 AlC MAX phase thin films on MgO(111) and Al2 O3 (0001). Control of the sample stoichiometry is achieved by elemental targets.